SWOT Analysis of Safranbolu City in Terms of Tourism - Dilek, Serkan; Keskingöz, Hayrettin (Center for Strategic Studies in Business and Finance SSBFNET, 2016)
Safranbolu is typical ottoman city with classical wooden houses, buildings and streets. With these characteristics Safranbolu located in world heritage list of UNESCO. Tourism is one of the most important activities in Safranbolu economy. Safranbolu is competing with its rivals to attract more visitors and earn more income from tourism. Though Safranbolu hosts many visitors, we can’t say that it seizes the opportunity to use its potential. Most probably, if Safranbolu uses all of its potential city can host more visitors and earn more from tourism. Our aim is to reveal strong and weak sides of Safranbolu city, opportunities and threads in this competition. By this way, Safranbolu can activate its potential and get more profit from tourism. To this aim, we conducted a survey to owner and administrators of Safranbolu touristic enterprises and analyses the results. We revealed interesting results about Safranbolu Tourism sector.
Keywords: 11. Sustainability; 3. Good health